Perceptions, problems faced and coping behaviour : a qualitative exploration among patients with breast cancer attending Hospital USM, Kubang Kerian, Kelantan - Jafar, Noor Hayati (2018)
Patients with breast cancer face many challenges which include coming to terms with the diagnosis, managing treatment regimens, dealing with the side effects of treatment, conducting self-care and rehabilitation. In addition, the underlying belief of the disease influenced their health seeking behaviours. Each individual may have different coping strategies in order to overcome her problem. The study aimed to explore perceptions, problems, and coping behaviours among patients with breast cancer, and to develop Self-study Health Education Module for patients with breast cancer. Patients were purposively recruited from the Outpatient Oncology Clinic, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan, Malaysia. Selected patients were interviewed in-depth until saturation were achieved. All interviews were tape-recorded and transcribed verbatim. Qualitative data were managed by Nvivo 10.0 software. Descriptive analysis was performed using SPSS version 22. A total of 34 patients took part in the study. Majority were married (85.3%), Malay (88.2%), age between 40 to 59 years old (70.6%), secondary school education (73.5%), housewife (61.8%), diagnosed with right breast cancer (52.9%) and with monthly income of less than RM 1500 (67.6%). The qualitative findings were divided into three sections which included patients’ perceptions regarding breast cancer, their problems and coping behaviours in patients with breast cancer. The themes raised from patients’ perceptions regarding breast cancer were cancer is viewed cancer as a death penalty; cancer treatment is terrifying and cancer as curable disease. The themes emerged regarding problems faced among patients with breast cancer were emotional, physical, and social relationship changes, economical restraint, and prioritise traditional over modern medicine. Three main themes emerged regarding coping behaviours were emotional-focused coping, spiritual-focused coping and problem-focused coping. Based on the study findings and literature search, a new Self-study Health Education Module was developed. Eleven experts viewed the module as good, very informative, helpful, suitable to implement and easy to understand. Mean scores of evaluations ranged from 3.5 (graphics are interesting) to 4.2 (module in line with objectives). Ten patients viewed the module as good, very interesting, clear, helpful, and easy to understand. Mean scores of evaluations ranged from 4.2 (pictures are interesting) to 4.8 (information are sufficient, beneficial). Health professional should also spend more time on counselling, conducting seminar and others activities to educate and improve awareness regarding breast cancer.